Pharmacotherapeutic options for hepatitis B. (11th February 2016) - Chen, Yi-Cheng; Liaw, Yun-Fan
ABSTRACT: Introduction : Hepatitis B virus (HBV) is the driving force of disease progression in chronic hepatitis B. Patients with active HBV replication and/or significant liver disease require timely treatment. Currently, pegylated interferon-α (PEG IFN), entecavir (ETV) and tenofovir disoproxil fumarate (TDF) are the preferred first-line drugs.Areas covered : A finite course IFN-based therapy has modest response and may reduce cirrhosis or hepatocellular carcinoma development. Nucleos(t)ide analogs (Nuc) have excellent safety profile, cumulative or maintained response and long-term efficacy in terms of reduction or reversal of fibrosis, decrease in development of cirrhosis and its adverse sequalae. The optimal duration of Nuc therapy is unknown and a feasible stopping rule with off-therapy monitoring plan has been developed.Expert opinion : Choosing a drug to initiate therapy in a right patient at a right time should be primarily based on the prospect and likelihood for improved outcomes. Nuc is the only choice for patients with hepatic decompensation, pregnant women and those about to receive immune/chemotherapy or organ transplantation. IFN-based therapy is preferred in patients with compensated liver disease, particularly in young patients, females of childbearing age. The development of new drugs and new strategies is the highest priority in further improving the outcomes of treatment.